Development and validation of rubrics to measure student's activities in the Natural Sciences - Ejem, Lynnette A. (Bukidnon State University Library Research Journal, 2008)
The researchers developed five rubrics as assessment tools in scoring students’ oral presentation, guided laboratory activity, portfolio, essay in a written test an write-up of an investigatory project in the natural sciences. The rubrics were developed based on criteria usually used in assessing such activities of students. Descriptors for criteria were made to guide the potential-teacher users in scoring objectively the work of the students. The developed rubrics were subjected to a validation process to refine its features. The panel of experts evaluated the rubrics with respect to content accuracy, clarity and appropriateness of the materials. The rubrics were also evaluated by the potential teacher-users. The respondents’ feedback were analyzed through the range of scores and means. The results of the evaluation revealed that the developed materials satisfy the provision set in the criteria. Evaluation showed that the contents of the rubrics are accurate, clear and appropriate. The researchers considered the qualitative comments and suggestions of the experts and potential-teacher users in the revision of the rubrics. The opinions of students on the developed rubrics were also analyzed. Results revealed that students found the rubrics very interesting, very relevant and objective in scoring students’ activities. Rubrics therefore can be (a) developed based on certain criteria that need to be assessed; (b) validated by a panel of experts; (c) revised and refined based on the quantitative and qualitative feedback of the experts; the potential-teacher implements and the potential student-users. It is therefore recommended that the developed rubrics be used in science classes to provide an objective tool in assessing students’ activities. The rubrics can be further revised through more quantitative feedback, which could be possibly obtained through the experimental study on their effectiveness as assessment tools in the sciences.